The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1177/2050312118759444
|View full text |Cite
|
Sign up to set email alerts
|

Hospital and clinical care costs associated with atrial fibrillation for Medicare beneficiaries in the Cardiovascular Health Study and the Framingham Heart Study

Abstract: Background:Atrial fibrillation is increasingly prevalent as the US population ages and is associated with significant morbidity and mortality. Care for patients with atrial fibrillation can be costly, US health care costs are comparatively high, and there are few cost estimates available that incorporate detailed measurement of comorbidities and their effects on costs.Methods and Results:In the Cardiovascular Health Study and the Framingham Heart Study, participants aged 65 years or older with newly diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Noteworthy, AF remained significantly associated with an increased risk of death even after controlling for cardiovascular comorbidities (2,3). AF is also associated with an estimated incremental cost of US$18,601 in hospital and clinical care in the year after diagnosis, even after accounting for age, time period, and comorbidities (4).…”
Section: Introductionmentioning
confidence: 98%
“…Noteworthy, AF remained significantly associated with an increased risk of death even after controlling for cardiovascular comorbidities (2,3). AF is also associated with an estimated incremental cost of US$18,601 in hospital and clinical care in the year after diagnosis, even after accounting for age, time period, and comorbidities (4).…”
Section: Introductionmentioning
confidence: 98%
“…While a few studies have been conducted that evaluated AC treatment of patients with AF in the outpatient setting and found relatively poor compliance with treatment guidelines, although utilization of DOACs is increasing in the USA 17 , little is known of inpatient AC treatment practices, especially in regard to parenteral AC utilization. Furthermore, the incremental healthcare costs of AF patients compared to those without the condition are rising in the USA, with a significant amount of the total cost attributed to costs for hospitalizations for cardiovascular, stroke, and bleeding events 18,19 Given the growing clinical and economic burden of AF, it is important to have a greater understanding of the treatment patterns of hospitalized patients with AF. Thus, in this study we evaluated utilization of ACs and the predictors of treatment of patients with a diagnosis of AF during a hospital stay in the USA from 1 January 2016 through 30 September 2017, a very recent time period in which warfarin, dabigatran, rivaroxaban, and apixaban were all available in the USA for the indication of stroke risk reduction in patients with AF.…”
Section: Introductionmentioning
confidence: 99%
“…13 Hospitalizations for AF have increased markedly and costs for AF treatment have soared. 14 Recent reports suggest that improving self-management of risk factors for AF such as hypertension, lipids, obesity, elevated blood glucose, and increasing physical activity plays an important role in stemming progression of AF and are associated with lower costs for AF-related care. 15 17 Langseth et al reported that engaging in shared decision making for treatment options resulted in lower treatment costs.…”
Section: Introductionmentioning
confidence: 99%